Studi Perbandingan Mekanisme Pengujian Undang-undang Terhadap Undang-undang Dasar Oleh Mahkamah Konstitusi Di Indonesia dan Jerman: A Comparative Study of the Judicial Review by The Constitutional Courts in Indonesia and Germany - Hamdy Mubarok; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2024)
The existence of a mechanism for judicial review of laws against the Constitution is a fundamental aspect that ensures all legislation is aligned with the principles of the Constitution. This mechanism upholds the supremacy of the Constitution, protects the constitutional rights of citizens from potential violations that may occur through legislation that does not comply with constitutional provisions. In Indonesia, the Constitutional Court is responsible for assessing the constitutionality of laws based on the 1945 Constitution. In Germany, this is carried out by the Federal Constitutional Court (Bundesverfassungsgericht), which has the authority to review laws against the Grundgesetz (German Constitution). The research problem in this study is how the mechanism of judicial review of laws against the Constitution is carried out by the Constitutional Court in Indonesia and Germany, and how the differences and similarities in judicial review mechanisms are based on the law in Indonesia and Germany. This research uses secondary data sources and is therefore normative legal research, with a descriptive-analytical nature and conclusions drawn using deductive logic. The result and the conclusion reached is that the German Constitutional Court has broad authority, including the review of both abstract and concrete norms, and its decisions are both final and binding.